The Influence of Compensation on Employee Retention and Job Satisfaction as Mediating Variables in Generation Z - Adiatma, Irsyad; Wahyono, G. Budi; Akbar, M. Taufik; Kurniawan, M. Yusuf; Mulyono, Sugeng (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study investigates how salary influences work satisfaction and retention among Generation Z employees in Surabaya, using job satisfaction as a mediator. The study uses an explanatory quantitative method to address high turnover rates, which are connected to wage discontent and limited career advancement. Questionnaires were used to collect data from 80 respondents, which were then analyzed with multiple linear regression, t-tests, and Sobel tests. The results reveal that salary has a favorable and considerable impact on both work satisfaction and retention. Job satisfaction has a favorable influence on retention and serves as a mediator between salary and retention. Finally, greater remuneration increases job happiness, which enhances Generation Z employee retention, emphasizing the need of competitive and equitable pay practices.